PENYUSUNAN ASET MODUL DIGITAL INOVASI LOKAL PASTRY SEBAGAI SARANA PUBLIKASI DIKALANGAN MAHASISWA SENI KULINER POLIMEDIA - Anggraeni Stj, Rr Christiana Mayang; Bellia Annishia, Fristi; Rosdiana Aprilia, Lu'luwatin (Jurnal Ilmiah Publipreneur, 2024)
Currently, the Industrial Revolution 4.0 is one of the big challenges facing Indonesia. The changes that occur in this era encourage society to carry out relevant innovations. Pastry products are still the favorites of many people in Indonesia. However, most of the raw materials used in these products come from imports, which can have a negative impact on the national economy. Considering Indonesia's abundant wealth of local food ingredients, there is great potential to replace imported ingredients with local ingredients in patisserie products. However, literacy regarding the use of local ingredients in making pastry is still very limited. Apart from that, there are no adequate means of publication among students of the Polimedia culinary arts study program. Therefore, this research aims to develop a publication facility asset in the form of a digital module that innovates the use of local materials in making pastry. The data collection method uses descriptive quantitative with a Likert scale, a publication test is carried out using a form to determine the level of usefulness of preparing digital module assets that have been published for Polymedia Culinary Arts students. The results obtained from the publication of digital module assets were accepted by Polimedia Culinary Arts Students at 88.5%.